URBAN AGRICULTURE ACTIVITY AND ITS POTENTIALS TO ERADICATE URBAN POVERTY IN JAKARTA - Galuh S Indraprahasta; Imas Agustina (Diponegoro University, 2012)
Rapid urbanization has affected urban areas in developing countries, including in Jakarta, in several ways. One of the impacts is the increasing number of poor inhabitants. Urban agriculture is recently re-raised as one of the answers for eradicating urban poverty, a condition that has an effect on, among other, food crisis. This paper aims to identify the potentials of urban agriculture development in Jakarta by learning from several best practices in other countries. This study employs qualitative descriptive analysis by considering precondition factors for urban agriculture development, most notably physical, institutional, and socio-economic factor. It can be concluded, from many cases, urban agriculture in Jakarta has, either directly or indirectly, impacts on people’s livelihood.